The Role of Law On the Implementation of Green Banking in Indonesia - Ria Safitri; Hartiwiningsih Hartiwiningsih; Hari Purwadi (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2019)
Abstract: The Economic development in Indonesia shows significant results, yet it has a negative impact towards the environment. The trouble is that if the bank has provided credit or financing to customers, it turns out that the credit recipient company discharges waste into the river or other actions that undermine the environment. Do banks have helped in financing environmental damage? Then how was the bank's responsibility for credit channeled to polling debtors? Economic development cannot be separated from bank institutions as an intermediary institution which has become one of the drivers of the economy and business so that it has a strategic role that can be used to achieve certain goals. One of the objectives of development is environmental sustainability. In order to espouse environmental preservation, the pattern of green banking can be applied, but only a small number of conventional banks and Islamic banks implement it in credit assessment terms. The pattern of green banking practice that can be realized in each credit agreement and financing at the bank, among others: administrative patterns, associative patterns, incentive patterns and evaluative patterns. Those patterns can be implemented with great awareness and responsibility from all banks in Indonesia.Keywords: law, bank, green banking Abstrak: Pembangunan ekonomi di Indonesia menunjukkan hasil yang cukup signifikan, akan tetapi menghasilkan dampak buruk terhadap lingkungan hidup. Permasalahannya yaitu apabila bank sudah menyalurkan kredit atau pembiayaan kepada nasabah yang ternyata perusahaan penerima kredit melakukan pembuangan limbah ke sungai atau kegiatan lainnya yang merusak lingkungan. Apakah bank dapat dikatakan turut membiayai terjadinya kerusakan lingkungan? Lalu bagaimana tanggungjawab bank terhadap kredit yang disalurkan pada debitur pencemar? Pembangunan ekonomi tidak dapat dilepaskan dari lembaga bank sebagai intermediary institution yang merupakan salah satu penggerak ekonomi dan bisnis sehingga memiliki peran strategis yang dapat digunakan untuk mencapai tujuan tertentu. Salah satu tujuan pembangunan adalah kelestarian lingkungan hidup. Dalam rangka menunjang pelestarian lingkungan hidup, pola green banking dapat diterapkan, akan tetapi hanya sebagian kecil bank konvensional dan bank syariah yang melaksanakannya dalam syarat penilaian kredit. Pola pelaksanaan green banking yang dapat direalisasikan dalam setiap perjanjian kredit dan pembiayaan pada bank, antara lain: pola administrative, pola asosiatif, pola pola insentif dan pola evaluative. Pola demikian dapat dilaksanakan dengan kesadaran dan tanggungjawab yang besar dari semua bank di Indonesia. Kata Kunci: Hukum, Bank, green banking